2017
DOI: 10.5935/abc.20170085
|View full text |Cite
|
Sign up to set email alerts
|

Global Longitudinal Strain or Left Ventricular Twist and Torsion? Which Correlates Best with Ejection Fraction?

Abstract: BackgroundEstimative of left ventricular ejection fraction (LVEF) is a major indication for echocardiography. Speckle tracking echocardiography (STE) allows analysis of LV contraction mechanics which includes global longitudinal strain (GLS) and twist/torsion, both the most widely used. Direct comparison of correlations between these novel parameters and LVEF has never been done before.ObjectiveThis study aims to check which one has the highest correlation with LVEF.MethodsPatients with normal LVEF (> 0,55) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The LV is composed of a complex three-layered myocardial structure leading to the longitudinal, circumferential and radial-directed deformation of the myocardium [24]. It is already known that the LV global strains strongly correlate with the EF; thus, the worsening of LV function is associated with decreased LV global strain parameters [10,25,26]. In our study, we found that the GLS, GCS and GRS gradually decreased as LV function worsened.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The LV is composed of a complex three-layered myocardial structure leading to the longitudinal, circumferential and radial-directed deformation of the myocardium [24]. It is already known that the LV global strains strongly correlate with the EF; thus, the worsening of LV function is associated with decreased LV global strain parameters [10,25,26]. In our study, we found that the GLS, GCS and GRS gradually decreased as LV function worsened.…”
Section: Discussionsupporting
confidence: 54%
“…These conflicting results could be due to the non-linear relationship between LV ejection fraction and GLS, namely, there is a stronger correlation between these two parameters at lower EF, and the curve flattens when the EF is higher than 50%. Thus, in this latter case, GLS can vary more with less effect on LV EF [25,26].…”
Section: Discussionmentioning
confidence: 92%
“…Left ventricular (LV) twist is the rotational movement of the LV along its longitudinal axis and results from the net difference between the torsional angles of the apical and basal rotations 11 13 . LV twist can robustly estimate myocardial function, expressed as LVEF 14 16 in some studies or dP/dt max in others 17 20 . LV untwisting rate provides the atrio-ventricular pressure gradients which assist cardiac chambers to fill during the early phase of relaxation 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…GLS by STE has a strong positive correlation with LVEF, especially in LV systolic impairment. 12 Santoro et al 13 found that in severe MR, both LVEF and GLS are independently associated with LV and LA size, but only GLS is related to SPAP suggesting GLS to be a powerful predictor of cardiac damage. In addition, GLS offers an angle-independent assessment of myocardial deformation, with recent reports showing better reproducibility and reliability compared with LVEF.…”
Section: Introductionmentioning
confidence: 99%